Catalytic properties of Sr1−xCexWO4: The role of mixed conduction in methane oxidation. (16th August 2018) - Damascena dos Passos, Rafael Hernandez; Pereira de Souza, Carlson; Leroux, Christine; Arab, Madjid
Abstract: The catalytic efficiency of ternary strontium cerium tungstate Sr0.5 Ce0.35 WO4, for the production of syngas through methane oxidation, was investigated and compared to those of binary strontium tungstate SrWO4 . Total and partial oxidation reactions were observed for both samples in the temperature range 600–750 °C under CH4 /dry air flux. At high CH4 concentration and low temperature with the ternary tungstate as catalyst, the partial oxidation, leading to CO/H2, prevails. This indicates the potentiality of the new strontium cerium tungstate scheelite compound for the catalysis of CH4 . Sr0.5 Ce0.35 WO4 and SrWO4 exhibit different conduction mechanisms. Conduction in the binary compound is related to the overlapping large polaron tunneling model, whereas conduction in the ternary one is due to a correlated barrier hopping phenomenon. The activation energies, in the low temperature range where the partial oxidation occurs, are significantly lower for the ternary compound than for the binary one. These electrical tendencies favor both partial and total oxidation of methane. The correlated barrier hopping conduction in the ternary compound leads to a better partial oxidation rate than conduction through large polaron tunneling. Graphical abstract: Highlights: Oxidation of CH4 into CO/H2 was catalyzed by Sr0.5 Ce0.35 WO4 at 650 °C, one atm. The complete decomposition of methane occurred at 750 °C through total oxidation. Substitution of Sr 2+ by Ce 3+ in Sr0.5 Ce0.35 WO4 increased the total conductivity. Conduction in Sr0.5 Ce0.35 WO4 is based on correlated barrier hopping of electrons.